2009
DOI: 10.1149/1.3049349
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Reduction Process of Sb(III) on Au Electrode Investigated by CV and EIS

Abstract: The electrochemical reduction processes of Sb(III) on Au electrode were studied by cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS) electrochemical measurements. The CV analyses reveal that the electrochemical reduction of SbnormalO+ on Au electrode includes three parts: the irreversible reduction of adsorbed SbnormalO+ , the reversible underpotential deposition (UPD) of dissociative SbnormalO+ , and the irreversible overpotential deposition of dissociative SbnormalO+ . Combining t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 26 publications
1
21
0
1
Order By: Relevance
“…These findings are consistent with literature data for hydrogen evolution from simple acidic solutions on different substrates such as Au, Co, Ni, Sb and Te [31]. The current density for hydrogen evolution on each substrate is related to the binding energy between the substrate and hydrogen atoms [32].…”
Section: Hydrogen Evolutionsupporting
confidence: 91%
See 1 more Smart Citation
“…These findings are consistent with literature data for hydrogen evolution from simple acidic solutions on different substrates such as Au, Co, Ni, Sb and Te [31]. The current density for hydrogen evolution on each substrate is related to the binding energy between the substrate and hydrogen atoms [32].…”
Section: Hydrogen Evolutionsupporting
confidence: 91%
“…Recently, the reduction of Sb (III) in tartaric acid solution was studied by Li [32] who found that the vast majority of the deposit came from the reduction of Sb (III) complex. Similarly, since almost all Te (IV) is in a complex form, the limiting current for Te is bound to the diffusion of Te (IV) complex in the electrolyte to the cathode.…”
Section: Full Papermentioning
confidence: 99%
“…is so strong that the Au surface is covered with a partially filled monolayer of SbO ? as soon as the electrode is immersed in electrolyte [14,25]. Scanning electron microscopy (SEM) has also identified the formation of a compound at the Au-Sb interface involving at least two top layers of the Au surface [8], which proves furthermore the existence of strong interactions in the Au-Sb system.…”
Section: Electrochemical Treatment Of Au Surfacementioning
confidence: 99%
“…Scanning electron microscopy (SEM) has also identified the formation of a compound at the Au-Sb interface involving at least two top layers of the Au surface [8], which proves furthermore the existence of strong interactions in the Au-Sb system. Therefore, the interpretation of the CV is complicated by other processes that precede or occur simultaneously with Sb thin film [8,14,25]. Although peak D 1 can be seen at all sweep rates, it is more easily detected at higher sweep rates.…”
Section: Electrochemical Treatment Of Au Surfacementioning
confidence: 99%
See 1 more Smart Citation